INTERPRETATION OF COAL POTENTION USING GROUND PENETRATING RADAR (GPR) METHOD - Wahidah, Rohmatul; Basid, Abdul (Jurnal Neutrino, 2017)
Coal exposure founded at Klatak Kebo Ireng village in Besuki Tulungagung precisely in the vicinity of the river. Energy needs is increasing so the coal used for one of alternative energy source that can be used by society. This study was conducted to determine of the potential distribution coal modeling on geological structure. Identification of coal structure is using Ground Penetrating Radar (GPR) 2005 it conducted because this method is more suitable for shallow of surveys. The location for taking data is around the river that showed to exposure. There are 5thÂ lines of taken data with length about 50 until 100 meters. Data processing was done using of software Future series 2005. The data displayed with software in the color pattern to obtain based on the constant of dielectric and conductivity. The results of interpretation study are the data indicates that there is a coal on the overall trajectory. Only in 2ndÂ track contain little of coal. The Coal layers are appear in processing the results of data is thickness about 6 at the top. In the area of study also found the cavity (cavity area) which contained of several tracks. On the bottom of the track there is a pattern of coal reddish of yellow color which indicates that material contains of minerals.